Research on the influence mechanism of food packaging on consumers' behavioral intention to refuse food waste based on behavioral reasoning theory - Mu, Juncheng; Zhou, Linglin; Yang, Chun (Frontiers in Psychology, 2025)
Given the escalating global concern regarding food waste, food packaging emerges as a critical area for intervention. Existing research, however, predominantly concentrates on consumer attitudes, offering limited insight into the role of food packaging in mitigating food waste. To address this gap, this study employs the BRT model, incorporating the variable of behavioral rationality into traditional theory and integrating values as a preceding variable. It integrates consumer values, behavioral rationality, attitudes, and behavioral intentions to explore the influence mechanism of food packaging on consumer behavior, explaining behavioral intentions through supporting/rejecting reasons. The study investigates how visual attributes, functionality, environmental sustainability, and social attributes within supporting reasons positively influence consumers' attitudes and behavioral intentions to reject food waste. Conversely, it investigates how information overload, functional deficiencies, inappropriate sizing, and high cognitive load within rejection reasons negatively impact these attitudes and intentions. By dissecting the positive and negative impacts of food packaging attributes on consumer attitudes and behavioral intentions across supporting and rejecting reasons, this research aims to identify key design factors for food packaging. This will fill existing research gaps, provide a theoretical foundation for food packaging design, and encourage consumers to adopt positive behaviors that reduce food waste. The findings indicate that: (1) consumer values significantly influence different behavioral attitudes; (2) supporting reasons related to food packaging positively impact the rejection of food waste behavior, while rejecting reasons have the opposite effect; (3) both positive and negative reasons significantly influence consumer attitudes and behavioral intentions, highlighting the need to optimize design elements in food packaging to positively influence consumer behavior; (4) packaging design factors have a more significant impact on intentions to conserve food than consumer attitudes themselves. This study extends the Behavioral Reasoning Theory (BRT) to understand food packaging's influence on consumer behavior, addressing contextual factors within BRT. Furthermore, it provides a scientific basis for food companies to optimize packaging design, which has practical implications for mitigating global food waste.